In situ Grown Pyramid Structures of Nickel Diselenides Dependent on Oxidized Nickel Foam as Efficient Electrocatalyst for Oxygen Evolution Reaction. (1st July 2016) - Li, Xiao; Han, Guan-Qun; Liu, Yan-Ru; Dong, Bin; Shang, Xiao; Hu, Wen-Hui; Chai, Yong-Ming; Liu, Yun-Qi; Liu, Chen-Guang
Graphical abstract: Highlights: Novel NiSe2 pyramids on oxidized nickel foam were in situ synthesized. The growth mechanisms of NiSe2 pyramids have been discussed. NiSe2 pyramids as electrocatalysts for OER showed better activity than NiSe. The enhanced properties of NiSe2 pyramids for OER were explained in details. Abstract: In situ grown pyramid structures of nickel diselenides (NiSe2 ) have been synthesized using oxidized nickel foam (NF (Ox)) as substrate by a facile solvothermal selenization. XRD results show that NiSe phase on NF and NiSe2 phase on NF (Ox) have been obtained after the identical selenization process, respectively. The nanorods morphology of NiSe on NF and pyramid structure of NiSe2 on NF (Ox) have been revealed by SEM images. The different structure and morphology of NiSe/NF compared with NiSe2 /NF (Ox) can be ascribed to the oxidation pretreatment of NF which affiliates the formation of ultrathin β-Ni(OH)2 nanosheets on NF. The electrochemical measurements for oxygen evolution reaction (OER) exhibit an enhanced electrocatalytic activity of NiSe2 /NF (Ox) with onset potential of 1.54 V (vs. RHE) and small Tafel slope of 96 mV dec −1 . Moreover, NiSe2 /NF (Ox) possesses lower charge-transfer resistance (Rct ) indicating a faster electron transfer rate than NiSe/NF. The excellent stability further confirms the improved elctrocatalytic performance of NiSe2 /NF (Ox). We speculate that the high Ni 2+ proportion and octahedral structure of NiSe2 may be the keys for excellent electrocatalytic properties for OER.